Perencanaan Strategis Sarana dan Prasarana Penunjang Proses Pendidikan - Beni Chandra Purba (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2024)
Strategic planning of educational support facilities and infrastructure constitutes an essential aspect in enhancing the overall quality and efficacy of educational systems. The availability and suitability of educational facilities serve as critical determinants influencing the smooth execution of teaching and learning activities, as well as the attainment of long-term institutional objectives. A frequent challenge encountered by educational institutions is the discrepancy between actual needs and the allocation of facilities and infrastructure, potentially leading to resource inefficiencies and degradation of educational service quality. Hence, an in-depth investigation into comprehensive strategic planning mechanisms is imperative to support precise, data-driven decision-making processes. This study employs a literature review methodology, integrating diverse scholarly sources, including indexed international journals, academic textbooks, national education policies, and other pertinent documents, to delineate an adaptive and sustainable conceptual framework for strategic planning. The findings affirm that the strategic planning process for educational facilities and infrastructure encompasses three principal stages: (1) empirical and prospective needs analysis, taking into account learner dynamics and curricular changes; (2) budget planning prioritizing fiscal efficiency and optimal resource utilization; and (3) procurement prioritization based on urgency, relevance, and impact on educational quality enhancement. The scope of facilities and infrastructure planned includes various categories ranging from physical infrastructure, consumables, immovable assets, to modern educational technology devices. The novelty of this research lies in the development of a holistic and participatory strategic planning model that accommodates the needs of all stakeholders and adapts to the evolving global educational landscape. Practical implications of this study are anticipated to reinforce governance in the procurement of educational facilities and infrastructure, ensuring effectiveness, transparency, and sustainability, while simultaneously supporting national educational transformation toward superior quality and heightened competitiveness.